38. Different behavior of cerebrospinal fluid amyloid-β and tau levels in patients with post-traumatic disorders of consciousness. Issue 12 (December 2017) - Bagnato, S.; Andriolo, M.; Boccagni, C.; Sant'Angelo, A.; D'Ippolito, M.E.; Galardi, G.
Abstract : Traumatic brain injury (TBI) is a major risk factor for Alzheimer disease (AD). Although the mechanisms that lead to AD after a TBI are largely unknown, changes in amyloid- β (A β ) metabolism and abnormal tau phosphorylation are probably involved. In this study, we evaluated A β 1 - 42, total tau (t-tau), and phosphorylated tau (p-tau) levels in the cerebrospinal fluid (CSF) of 15 patients who developed a prolonged disorder of consciousness after a severe TBI (mean time from TBI 271.6 ± 176.5 days; range 92–578 days). Reduced A β 1 - 42 levels (cohort median value 258 pg/ml, range 90–833.6 pg/ml) were observed in 14/15 patients (93.3%) with severe post-TBI disorders of consciousness. Normal t-tau levels (median 95.2 pg/ml, range 52–256.9 pg/ml) were found in all patients. Normal p-tau levels (median 22.2 pg/ml, range 14–72 pg/ml) were observed in 14/15 patients, while 1 patient had a p-tau level slightly increased. In conclusion, the present findings show that reduced CSF A β levels are not paralleled by significant changes in t-tau and p-tau levels; these results suggest that treatments aimed to prevent chronic neurodegeneration and AD risk after a severe TBI may be better targeted on A β than tau.